2009
DOI: 10.1007/s00168-009-0292-9
|View full text |Cite
|
Sign up to set email alerts
|

How does industry specialization affect the efficiency of regional innovation systems?

Abstract: This study analyzes the relationship between the specialization of a region in certain industries and the efficiency of the region in generating new knowledge. The efficiency measure is constructed by relating regional R&D input and output. An inversely u-shaped relationship is found between regional specialization and R&D efficiency, indicating the presence of externalities of both Marshall and Jacobs' type. Further factors influencing efficiency are externalities resulting from high R&D intensity of the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 48 publications
3
46
1
4
Order By: Relevance
“…Specifically, we find that industry concentration in Eastern German regions beyond a certain maximum level seems to decrease regional innovative performance. This result reinforces prior research, where such an inverse-U relationship has been detected (Folta, Cooper and Baik 2006;Fritsch and Slavtchev 2009). In other words, if manufacturing industries in Eastern Germany exhibit an exceedingly high degree of concentration in a specific region, this has negative effects on the innovative performance of that region.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Specifically, we find that industry concentration in Eastern German regions beyond a certain maximum level seems to decrease regional innovative performance. This result reinforces prior research, where such an inverse-U relationship has been detected (Folta, Cooper and Baik 2006;Fritsch and Slavtchev 2009). In other words, if manufacturing industries in Eastern Germany exhibit an exceedingly high degree of concentration in a specific region, this has negative effects on the innovative performance of that region.…”
Section: Discussionsupporting
confidence: 89%
“…industry concentration) are present only in the service sector, but not for manufacturing industries. A recent study by Fritsch & Slavtchev (2009) relates industry concentration to the efficiency of regional innovation systems (measured by the number of disclosed patent applications per Planning Region). The authors find an inverse-U relationship, which means regional industry concentration beyond a maximum seems to lower regional innovative performance.…”
Section: Iwh-diskussionspapiere 8/2009mentioning
confidence: 99%
“…Inter-and transdisciplinary research settings anchor research projects and support the implementation of results. This has also been confirmed for applied research versus basic research projects (Fritsch and Slavtchev 2010). Overall the contribution of research to RTPS can be seen in the shaping of public opinion and discourse, scientific substantiation of political strategies, expert know how, and concrete scientific contributions to process or product innovations (e. g. in the field of renewables).…”
Section: Discussionmentioning
confidence: 68%
“…As states belong in the same country and, therefore, share common institutions, among other things, an interesting issue that arises is whether small institutional and networking differences across regions have different innovation implications. 29 A related study of Fritsch and Slavtchev (2010) has also analyzed the relationship between the specialization of a region in a panel of german industries and the efficiency of the region in generating new knowledge. Externalities resulting from high R&D intensity of the local private sector as well as knowledge from local public research institutions are identified to positively influence regional innovation efficiency.…”
Section: Resultsmentioning
confidence: 99%